Inhibitory action of methylene bisphosphonic acid on metabolic activity and viability of J774A.1 cells - D. O. Labudzynskyi; E. P. Pasichna; O. I. Krynina; М. M. Veliky (The Ukrainian Biochemical Journal)
Bisphosphonates (BPs) are primary agents in the current pharmacological arsenal against osteoclast-related bone loss due to osteoporosis, Paget’s disease and bone tumors. Due to the lack of complete understanding of the molecular mechanism of their action in bone tissue and the overlap of key properties between BPs of different generations, integral studies of BPs inhibitory and antiresorptive properties are relevant today. The present work was carried out to establish a comprehensive study of the inhibitory effects of methylene bisphosphonic acid (MBPA) on the mevalonate pathway, metabolic activity and cell death in vitro compared to zoledronic acid (Zol). Farnesyl pyrophosphate synthase activity of MBPA-treated J774A.1 cells was inhibited by 80%, compared with a 79% reduction in Zol-treated samples. The ability of MBPA to decrease the percentage of viable cells in culture is slightly lower compared with Zol. After 24 h of incubation with lowest concentration, the percentage of inhibition of metabolic activity was 10.6 and 25%, respectively. After 48 h, these values were 34.8 and 55.6%, respectively. The inhibitory effects of MBPA and Zol on the intensity of incorporation of radioactively labeled precursor [14C]-acetate to the cholesterol fraction were 76.2 and 59.1%, respectively. In the case of isoprenoid fraction, the inhibitory effects were 40.9% and 51.2%, respectively. MBPA and Zol differently induced apoptosis in the J774A.1 cells culture, increased count of apoptotic cells in 2.4 and 6.3 times, and also increased the number of propidium iodide-positive cells in 7.4 and 19 times, respectively. MBPA and Zol also increased the number of TUNEL-positive cells in macrophage culture in 2.6 and 5 times, respectively. Zoledronate significantly reduced carbonic anhydrase 2 and nuclear factor of activated T-cells 1 gene expression levels compared to the MBPA action. Thus, the use of MBPA in future research and therapy of both cancer and osteoporosis looks promising due to lower cytotoxicity, high efficiency of mevalonate pathway inhibition and the possibility of dosage variation.